A Place for Viruses on the Tree of Life - Harris, Hugh M. B.; Hill, Colin (Frontiers in Microbiology, 2021)
Viruses are ubiquitous. They infect almost every species and are probably the most abundant biological entities on the planet, yet they are excluded from the Tree of Life (ToL). However, there can be no doubt that viruses play a significant role in evolution, the force that facilitates all life on earth. Conceptually, viruses are regarded by many as non-living entities that hijack living cells in order to propagate. A strict separation between living and non-living entities places viruses far from the ToL, but this may be theoretically unsound. Advances in sequencing technology and comparative genomics have expanded our understanding of the evolutionary relationships between viruses and cellular organisms. Genomic and metagenomic data have revealed that co-evolution between viral and cellular genomes involves frequent horizontal gene transfer and the occasional co-option of novel functions over evolutionary time. From the giant, amoeba-infecting marine viruses to the tiny Porcine circovirus harboring only two genes, viruses and their cellular hosts are ecologically and evolutionarily intertwined. When deciding how, if and where viruses should be placed on the ToL, we should remember that the Tree functions best as a model of biological evolution on Earth, and it is important that models themselves evolve with our increasing understanding of biological systems.